STUDY OF THE EFFICIENCY OF APPLICATION OF LACTIMAC FORTE IN COMPLEX TREATMENT OF PATIENTS WITH HIV INFECTION AND DISORDERS OF THE MICROBIAL LANDSCAPE OF THE INTESTINAL - Мироник, О.; Давыденко, Е. (SWorldJournal, 2021)
The article presents the results of studying the effectiveness of the use of the drug Laktimak Forte in the complex treatment of HIV infection. Shown the beneficial effect of the drug on the reduction and severity of diarrheal syndrome, normalization of